Whole-Blood Transcriptome Analysis of Feedlot Cattle With and Without Bovine Respiratory Disease - Jiminez, Janelle; Timsit, Edouard; Orsel, Karin; van der Meer, Frank; Guan, Le Luo; Plastow, Graham (Frontiers in Genetics, 2021)
Bovine respiratory disease (BRD) is one of the main factors leading to morbidity and mortality in feedlot operations in North America. A complex of viral and bacterial pathogens can individually or collectively establish BRD in cattle, and to date, most disease characterization studies using transcriptomic techniques examine bronchoalveolar and transtracheal fluids, lymph node and lung tissue as well as nasopharyngeal swabs, with limited studies investigating the whole blood transcriptome. Here, we aimed to identify differentially expressed (DE) genes involved in the host immune response to BRD using whole blood and RNA sequencing. Samples were collected from heifers (average arrival weight = 215.0 ± 5.3 kg) with (n = 25) and without (n = 18) BRD at a commercial feedlot in Western Canada. RNAseq analysis showed a distinct whole blood transcriptomic profile between BRD and non-BRD heifers. Further examination of the DE genes revealed that those involved in the host inflammatory response and infectious diseases pathways were enriched in BRD animals, while gene networks associated with metabolism and cell growth and maintenance were downregulated. Overall, the transcriptome profile derived from whole blood provided evidence that a distinct antimicrobial peptide driven host immune response was occurring in the animals with BRD. The blood transcriptome of BRD animals shows similarities to the transcriptomic profiles obtained from lung and bronchial lymph nodes in other studies. This suggests that the blood transcriptome is a potential diagnostic tool for the identification of biomarkers of BRD infection and can be measured in live animals and used to further understand infection and disease in cattle. It may also provide a useful tool to increase the understanding of the genes involved in establishing BRD in beef cattle and be used to investigate potential therapeutic applications.